5-3(3m-4)=1

Simple and best practice solution for 5-3(3m-4)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-3(3m-4)=1 equation:


Simplifying
5 + -3(3m + -4) = 1

Reorder the terms:
5 + -3(-4 + 3m) = 1
5 + (-4 * -3 + 3m * -3) = 1
5 + (12 + -9m) = 1

Combine like terms: 5 + 12 = 17
17 + -9m = 1

Solving
17 + -9m = 1

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-17' to each side of the equation.
17 + -17 + -9m = 1 + -17

Combine like terms: 17 + -17 = 0
0 + -9m = 1 + -17
-9m = 1 + -17

Combine like terms: 1 + -17 = -16
-9m = -16

Divide each side by '-9'.
m = 1.777777778

Simplifying
m = 1.777777778

See similar equations:

| 0.15=x/30 | | 3y+1=54 | | 3+12t-3t^2=o | | 2.3X=10.4-2.9X | | 2.3X+1.3=8.8 | | -6.5X-1.6=-2.9X | | -12x^2+22x-6=0 | | 5.2X-1.6=8.8 | | 2x^24=25 | | 1y=2x-5 | | 3r^2+4r-16=0 | | n/11=19/22 | | 4.48x+4=20.0704+2x | | 2.3X-10.4=-2.9X | | 36b^3-16b= | | x+0.22x=1400 | | 9/z=3/13 | | 8x+12=10x-22 | | 7x-5=Ax+A+Bx-2B | | 0.0924=((3,14*x^2)/4)*1,5x | | 2(2x-5)=8x-6x | | 18=v+125 | | 9n^2=-16 | | 16k+24=0 | | 6pk-9k=4n+2nk | | 5x+4x-5=22 | | 6x-9=15(4+X) | | 1c-9.6=0 | | 5+(6a-2a)=(5a-11)-(6+3a) | | x^2+(m+1)x+4=0 | | 34=9x | | -32.4=-4.5t |

Equations solver categories